Civil society in global health policymaking: a critical review - Eduardo J. Gómez (BMC, 2018)
Abstract Background A social science approach to the study of civil society's role and influence in global health policymaking is a new area of scholarly research. In this article, I conduct a critical literature review to assess the recent research done on this topic. Main body I find that most research has been narrowly focused on the agenda-setting and policy implementation stages, failing to account for all stages of the policymaking process and civil society's role in it. Additionally, very little effort has been made to test and develop theoretical and analytical policymaking frameworks, clearly and consistently defining and conceptualizing civil society's role and influence in global health policymaking, provide methodological specificity and diversity, while emphasizing the importance of causal mechanisms. Conclusion I conclude by encouraging scholars to address these lacuna in the literature and to explore the utility of political science theory and alternative policymaking models to better define and explain the complexity of civil society's role and influence in global health policymaking processes.